Cognitive behavioural therapy strengthens Malaysia’s mental health landscape - Juferi, Noor Eszereen (Universiti Putra Malaysia, 2026)
Cognitive Behavioural Therapy (CBT) continues to gain recognition as one of the most effective psychotherapeutic approaches for addressing mental health issues in Malaysia, in tandem with growing public awareness of the importance of psychological well-being. Prof Dr Firdaus Mukhtar, a lecturer at the Department of Psychiatry, Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, said CBT is an evidence-based therapy that focuses on the relationship between an individual’s thoughts, emotions and behaviours.